Relationship between prognostic nutritional index and neutrophil lymphocyte ratio with overall survival in patients with metastatic colorectal cancer receiving regorafenib - KÖSTEK, OSMAN (My University, 2022)
Aim: In this study, we aimed to analyze the effect of prognostic nutritional index and neutrophile lymphocyte ratio on the overall survival (OS) in patients treated with regorafenib. Materials and Methods: Metastatic colorectal cancer (CRC) patients who treated with regorafenib between 2016 and 2020 in a single center were evaluated retrospectively. ROC analysis was used for neutrophile lymphocyte ratio (NLR’s) and prognostic nutritional index (PNI’s) optimum cut‑off value. The relationship between OS with PNI and NLR was investigated. Results: Fifty‑two patient’s data were analyzed. The median age was 57 years, 22 (41.5%) of the patients were female. The optimal cut‑off value of PNI for OS was 45.7 according to ROC curve analysis. The median NLR value was accepted as 2.7. Median OS was 8.3 months. Patients who have high PNI value than 45.7 had longer OS (12.09 months vs. 6.31 months hazard ratio [HR]: 0.37 95% confidence interval [CI]: 0.19–0.73 P = 0.003) and there was a tendency for longer OS with low NLR value then median (12.05 months vs. 6.14 months HR: 0.54 95% CI: 0.29–1.23 P = 0.057). Primary tumor resected patients had longer OS than nonresected patients (12.05 months vs. 6.30 months HR: 0.34 95% CI: 0.17–0.66 P = 0.001). In multivariate analysis, high PNI value more than 45.7 (HR: 0.40 95% CI: 0.18–0.88 P = 0.02) and resection of the primary tumor (HR: 0.40 95% CI: 0.21–0.80 P = 0.01) were the only independent factors for longer OS. Conclusion: Metastatic CRC patients with high pretreatment PNI and primary tumor resected are more likely to have longer OS with regorafenib. PNI is more reliable index than NLR to predict OS in metastatic CRC patients treated with regorafenib.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Disease control; neutrophil‑lymphocyte ratio; prognostic nutritional index